2021
DOI: 10.1093/jhered/esab004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Profiling Reveals Two Lineages of Sun Bears in East and West Malaysia

Abstract: Sun bear populations are fragmented and at risk from habitat loss and exploitation for body parts. These threats are made worse by significant gaps in knowledge of sun bear population genetic diversity, population connectivity, and taxonomically significant management units. Using a complete sun bear mitochondrial genome, we developed a set of mitochondrial markers to assess haplotype variation and the evolutionary history of sun bears from Peninsular (West) Malaysia, and Sabah (East Malaysia). Genetic samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 32 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…The Sunda clade includes sequences ( N = 15) from Borneo, Sumatra and Peninsular Malaysia (all part of Sundaland), but also from Thailand, and from three archival samples of unknown provenance (sample details in Table S1 ). This clade also gave rise to two major lineages, which diverged ~128 kya (CI 95 : 170–93 kya), that correspond to mtDNA lineages previously identified (Lai, Chew, et al, 2021 ): the Peninsular lineage and Sabah lineage (indicated in Figure 2 ). These two lineages have a large geographic overlap: both include sun bears from Sumatra, Peninsular Malaysia and Thailand.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The Sunda clade includes sequences ( N = 15) from Borneo, Sumatra and Peninsular Malaysia (all part of Sundaland), but also from Thailand, and from three archival samples of unknown provenance (sample details in Table S1 ). This clade also gave rise to two major lineages, which diverged ~128 kya (CI 95 : 170–93 kya), that correspond to mtDNA lineages previously identified (Lai, Chew, et al, 2021 ): the Peninsular lineage and Sabah lineage (indicated in Figure 2 ). These two lineages have a large geographic overlap: both include sun bears from Sumatra, Peninsular Malaysia and Thailand.…”
Section: Resultssupporting
confidence: 57%
“… Bayesian phylogenetic tree reconstructed using H. malayanus mitogenome sequences ( N = 35). Two main branches are labeled according to clade assignment, and previously reported lineages (Peninsula and Sabah; Lai, Chew, et al, 2021 ) are indicated. Sequences are labeled with sample ID and geographic origin (if known); text color of geographic origin follows the inset map (top left).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For decades, population genetics approaches have been deployed to inform species conservation efforts [1]. Molecular markers such as mitochondrial DNA sequences and microsatellites have been used to answer conservation genetic questions such as estimating relatedness between individuals [2,3] or effective population size [4,5], and ascertaining population structure to delineate conservation units [6,7]. In the past decades, genetic studies have also started to rely on the analysis of single nucleotide polymorphisms (SNPs), which are highly abundant across genomes (i.e.…”
Section: Introductionmentioning
confidence: 99%